Observing the Testing Effect using Coursera Video-Recorded Lectures: A Preliminary Study - Yong, Paul Zhihao; Lim, Stephen Wee Hun (Frontiers in Psychology, 2016)
We investigated the testing effect in Coursera video-based learning. One hundred and twenty-three participants either (a) studied an instructional video-recorded lecture four times, (b) studied the lecture three times and took one recall test, or (c) studied the lecture once and took three tests. They then took a final recall test, either immediately or a week later, through which their learning was assessed. Whereas repeated studying produced better recall performance than did repeated testing when the final test was administered immediately, testing produced better performance when the final test was delayed until a week after. The testing effect was observed using Coursera lectures. Future directions are documented.